PEMANFAATAN SAKARIN SEBAGAI ALTERNATIF PENGENDALI KOROSI BALING-BALING KAPAL - Nani Mulyaningsih; Hadyan Hadyan (Universitas Tidar, 2018)
Corrosion is a metallic interaction with the environment that causes damage to the metal. Corrosion can also occur in fishing vessels, which are generally made of low carbon steel. This happens because the propeller works in a corrosive environment. Then the need for an alternative corrosion control so that the component is durable. The purpose of this study was to find out how much corrosion rate the ship propellers produced after the addition of saccharin on the nickel electroplating process. This study was conducted by specimen electroplating nickel with the addition of saccharin variation of (0.6 gram; 0.8 gram; and 1 gram). Then the results in corrosion test using sea water media. The corrosion rate is calculated using the weight loss method. After the calculated corrosion rate, then the effectiveness of saccharin is calculated. The results showed that nickel electroplating specimens with addition of 0.6 gram saccharin variation resulted in a corrosion rate of 75 mpy, 0.8 gram saccharin yielded a corrosion rate of 83.14 mpy, saccharin 1 gram of corrosion rate of 90.56 mpy, while raw material corrosion rate of 117.73 mpy.